Food safety, consumer trust in livestock farmers and purchase likelihood - Yee, Wallace Man Shek (Cranfield University, 2002)
Food safety is an important issue facing consumers, the food industry and the government. Since consumers cannot themselves easily assess food safety risks, their perception of food safety is in part a matter of trust in the food chain. This study focuses on livestock farmers and investigates the causal relationship between the factors which determine consumer trust regarding food safety and in turn their purchase likelihood. The main research questions are: 1) What are the key factors which build consumer trust in this context? 2) What are the contributions of these factors to building consumer trust? 3) Is there any relationship between consumer trust and purchase likelihood? By integrating theories developed in several disciplines, six factors, namely: providing information, competence, integrity, benevolence, credibility and reliability were identified to have a strong influence on consumer trust in livestock farmers. An exploratory study in the form of face-to-face interviews was carried out to clarify the main concerns of livestock husbandry practices, and to identify the items to measure the causal factors of consumer trust in livestock farmers regarding food safety. Because the objectives set out in this study could not be achieved by using multiple regression, which could not handle latent variables, the conceptual model was tested with a quota sample of 194 individuals in the form of a Structural Equation Model using LISREL 8.30. It was proved successful in identifying the effects of the causal factors of trust to build consumer trust and in turn to affect purchase likelihood. The factor ‘providing information’ was identified to be a key factor by which trust is built and the features that lead to trust, namely: ‘competence’, ‘integrity’, ‘credibility’, ‘reliability’, and ‘benevolence’ were identified to be factors to build trust in livestock farmers. Representatives of the livestock industry were approached to confirm the relevance of the study and facilitate the interpretation of the findings. Though there is a limitation of its generalisation due to the sampling method, there is evidence that these factors are important to building consumer trust in livestock farmers regarding food safety. The evidence also suggests that there is a strong relationship between trust and consumer purchase likelihood. The research confirms that livestock farmers could draw benefit from strategies to increase their trustworthiness and in turn positively influence consumers’ purchasing decision. This study recommends further research to apply this model in other industries where the suppliers have little contact with consumers. The differences in trust building between cultures and the communication channels that livestock farmers representatives should used are also suggested for further study. Future research on how the food industry should respond to the change in consumer trust during periods of concern about food safety is also recommended. These are valid topics for future research and will provide potential benefits for consumers and food industry as a whole.
Keywords: Intensive farming